Development and Evaluation of a Quantitative PCR Assay Targeting Sandhill Crane (Grus canadensis) Fecal Pollution - Ryu, Hodon (American Society for Microbiology, 2012)
While the microbial water quality in the Platte River is seasonally impacted by excreta from migrating cranes, there are no methods available to study crane fecal contamination. Here we characterized microbial populations in crane feces using phylogenetic analysis of 16S rRNA gene fecal clone libraries. Using these sequences, a novel crane quantitative PCR (Crane1) assay was developed, and its applicability as a microbial source tracking (MST) assay was evaluated by determining its host specificity and detection ability in environmental waters. Bacteria from crane excreta were dominated by bacilli and proteobacteria, with a notable paucity of sequences homologous to Bacteroidetes and Clostridia. The Crane1 marker targeted a dominant clade of unclassified Lactobacillales sequences closely related to Catellicoccus marimammalium. The host distribution of the Crane1 marker was relatively high, being positive for 69% (66/96) of the crane excreta samples tested. The assay also showed high host specificity, with 95% of the nontarget fecal samples (i.e., n = 553; 20 different free-range hosts) being negative. Of the presumed crane-impacted water samples (n = 16), 88% were positive for the Crane1 assay, whereas none of the water samples not impacted by cranes were positive (n = 165). Bayesian statistical models of the Crane1 MST marker demonstrated high confidence in detecting true-positive signals and a low probability of false-negative signals from environmental water samples. Altogether, these data suggest that the newly developed marker could be used in environmental monitoring studies to study crane fecal pollution dynamics.